Learning With a Project Aproach: an experience of a pedagogical support for supervision and teacher development - Leal da Costa, Conceição (2014)
In this presentation, we intend introduce a work developed over the last two years. The project emerged, considering that the education of the most of us, influencing behaviors and learning, has allowed the reproduction of traditional teaching practices, in early childhood and in elementary schools. It started with empirical evidence of attitudes and beliefs that, in a recurring cycle of works and activities, seems to hamper, many times prevent, dialogical visions and practices in the classroom. The supervision process associated with teacher cooperation in the pre-service teacher education, have emerged opportunities of, in a search for promoting their working on projects, desired by them, achieving it through a structured in-service course at the University of Évora. Within this context, how professional development increases teachers knowledge and skills, changes their attitudes and beliefs, or both, has emerged as an important topic. The course: ―Learning with a project approach in early childhood and in elementary school‖, started with an emphasis placed on behaviors, doubts and professional experiences, and how cooperates and experienced teachers perceive the effectiveness of the strategies they use to promote and teach with a project approach. We argue that the use of teaching and learning dialogical model, based on learning by projects, working on meaningful activities, can also benefit teacher learning. We will introduce the route of two groups of teachers, demonstrating the way how they designed and accomplished their projects of learning, and the way given to the aggregate of their experiences. To outline future paths, in the way of some valid contributions for their lifelong learning and to change practices, we will sharing some reflections on the challenges, learning activities and core features of this course.